Distribution of ventilation and oxygenation in surgical obese patients ventilated with high versus low positive end-expiratory pressure: A substudy of a randomised controlled trial. Issue 11 (12th November 2022) - Ellenberger, Christoph; Pelosi, Paolo; de Abreu, Marcelo Gama; Wrigge, Hermann; Diaper, John; Hagerman, Andres; Adam, Yannick; Schultz, Marcus J.; Licker, Marc
Abstract : BACKGROUND: Intra-operative ventilation using low/physiological tidal volume and positive end-expiratory pressure (PEEP) with periodic alveolar recruitment manoeuvres (ARMs) is recommended in obese surgery patients. OBJECTIVES: To investigate the effects of PEEP levels and ARMs on ventilation distribution, oxygenation, haemodynamic parameters and cerebral oximetry. DESIGN: A substudy of a randomised controlled trial. SETTING: Tertiary medical centre in Geneva, Switzerland, between 2015 and 2018. PATIENTS: One hundred and sixty-two patients with a BMI at least 35 kg per square metre undergoing elective open or laparoscopic surgery lasting at least 120 min. INTERVENTION: Patients were randomised to PEEP of 4 cmH2 O ( n = 79) or PEEP of 12 cmH2 O with hourly ARMs ( n = 83). MAIN OUTCOME MEASURES: The primary endpoint was the fraction of ventilation in the dependent lung as measured by electrical impedance tomography. Secondary endpoints were the oxygen saturation index (SaO2 /FIO2 ratio), respiratory and haemodynamic parameters, and cerebral tissue oximetry. RESULTS: Compared with low PEEP, high PEEP was associated with smaller intra-operative decreases in dependent lung ventilation [-11.2%; 95% confidence interval (CI) -8.7 to -13.7 vs. -13.9%; 95% CI -11.7 to -16.5; P = 0.029], oxygen saturation index (-49.6%; 95% CI -48.0 to -51.3 vs. -51.3%; 95% CI -49.6 to -53.1; P < 0.001) and a lower driving pressure (-6.3 cmH2 O; 95% CI -5.7 to -7.0). Haemodynamic parameters did not differ between the groups, except at the end of ARMs when arterial pressure and cardiac index decreased on average by -13.7 mmHg (95% CI -12.5 to -14.9) and by -0.54 l min -1 m -2 (95% CI -0.49 to -0.59) along with increased cerebral tissue oximetry (3.0 and 3.2% on left and right front brain, respectively). CONCLUSION: In obese patients undergoing abdominal surgery, intra-operative PEEP of 12 cmH2 O with periodic ARMs, compared with intra-operative PEEP of 4 cmH2 O without ARMs, slightly redistributed ventilation to dependent lung zones with minor improvements in peripheral and cerebral oxygenation. TRIAL REGISTRATION: NCT02148692, https://clinicaltrials.gov/ct2